Association of CRP Levels in 3rd Trimester with Fetal Birth Weight in Normotensive and Preeclamptic Pregnant Females - Monika, Bushra Begun Ramejo, Saira Ghafoor, Nazia Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the level of C-reactive protein, which is an inflammatory marker, in pregnant women with pre-eclampsia and with normal blood pressure, and to assess its relationship with fetal weight at birth. Study design: An analytical and Cross-sectional study. Place and duration of study: In the Obstetrics and Gynecology department of Chandka Medical Hospital, Larkana and Murshid Hospital, Karachi for nine months duration from January to September 2021. Methodology: A total 70 cases of pre-eclampsia and 70 pregnant women with normal blood pressure participated, all in the 3rd trimester of gestation. All females were in the 20-40 years of age group and had a BMI ranging from 18 to 25. Highly sensitive levels of C-reactive protein (hsCRP) were evaluated using the Enzyme Link immunosorbent assay. Statistical analysis was performed with SPSS program 20.0. The values ​​were taken as significant at the significance level of 0.05. Results: C-reactive protein levels were significantly advanced in the pre-eclampsia group with a mean value of 8.4 (0.4 to 24.2) compared to 5.1 (0.21 to 10.1) mg / L in women with normal blood pressure (p-value <0.001). Spearman's correlation coefficient between birth weight and CRP was -0.405 in the pre-eclampsia group (p = 0.001) and 0.118 in the normal blood pressure group. In the group with pre-eclampsia, the birth weights of children were also significantly lower. High CRP levels in the preeclampsia group were negatively correlated with fetal birth weight. Conclusions: High levels of C-reactive protein in pregnant women with pre-eclampsia are part of the excessive systemic maternal inflammatory response and are associated with low fetal weight. Keywords: Pre-eclampsia. C-reactive protein. Pregnancy. Third trimester